Expect the Unexpected: My Little Pony: Friendship is Magic and the Creation of a Double Audience - Isabelle Licari-Guillaume (Transatlantica)
Popular and academic discussions of My Little Pony: Friendship is Magic often tend to contrast the “expected audience” of very young girls with an adult, mostly male “unexpected audience.” This polarizing view begs the question of what the various agents involved in the production of the series actually expect of their audience, and how such expectations are expressed through the material they produce and the type of behaviors they encourage. I argue that MLP: FiM is in fact the site of a complex combination of expectations (moral, commercial, and otherwise) that create a specific type of audience. Beyond their obvious commercial nature, the MLP: FiM show and comics are tied with ideological and legal concerns regarding the status of children’s entertainment, which is expected to protect and educate its audience. Moreover, the creators had their own set of expectations: they set out to question gender stereotypes by creating quality entertainment for girls that presented independence, solidarity, and individual development as positive values. The desire to reappraise girls’ entertainment helped create a franchise that was in fact transgenerational and encouraged different modes of participation, thus creating the conditions for the emergence of an older, more media-savvy fan audience.